Socioeconomic Inequality in Health Literacy, Self-Rated Health, and General Health in Arak, Iran: a Population-Based Cross-Sectional Study - Tayebeh Nadi; Jalal Poorolajal; Amin Doosti-Irani (Hamadan University of Medical Sciences, 2021)
Aims: Socioeconomic inequalities are major problems for public health in the communities. This study aimed to determine the socioeconomic inequality of health literacy (HL), self-rated health (SRH), and general health. Instrument & Methods: This cross-sectional study was performed in Arak city, Iran, in 2019. The Wealth index was created using the principal component analysis (PCA) based on participants' assets. HL was evaluated using a validated questionnaire in Iran. The general health was evaluated using the WHO general health questionnaire. The relative concentration index (RCI) was used to assess HL's inequality, SRH, and general health. The simple random sampling method was used. The results were reported at a 95% CI. Stata software 14.2 was used for data analysis. Findings: Overall, 750 adults with a mean±SD age of 34.76±9.82 participated in this study. The prevalence of poor SRH was 2.93 (95% CI: 1.94, 4.42). In general health domains, the highest poor prevalence was related to the feelings of sadness or depression in the 30 past days with 10.80% (95% CI: 8.77, 13.24). The total prevalence of poor health literacy was 25.60% (95% CI: 22.60, 28.85). In domains of poor general health, mobility, cognition, individual activities, and sleep disorders were significantly concentered among disadvantaged participants. Also poor health literacy was concentered among disadvantaged participants in term of wealth index and education, RCI=-0.21; 95% CI: -0.27, -0.14 and RCI= -0.25; 95% CI: -0.32, -0.19, respectively. Conclusion: Poor health domains such as mobility, cognition, individual activities, sleep, and poor health literacy were significantly concentrated among disadvantaged participants based on the wealth index and education.